ALGORITMA RETURN MAPPING UNTUK ANALISIS KELELEHAN MATERIAL ELASTOPLASTIK HARDENING AKIBAT PEMBEBANAN MULTIAKSIAL TEKAN - Jaya Ekaputri , Januarti
Abstrak A numerical scheme was employed for the analysis of elastoplastic problems. This scheme eventually becomes necessary to integrate the constitutive equations governing material behaviour. and return mapping to enforce the consistency conditions. The accuracy of numerical algorithms - the tangent radial return - is analysed for the Ottosen yield criterion with nonassociated flow rule.There are four explicit integration methods to solve return mapping problems: Forward Euler, Runge Kutta 2nd order, Modified Euler, and Runge-Kutta 4th order. The accuracy of model are being assessed through comparison with experimental results. These experimental results can be used to estimate the errors of various numerical algorithms used the finite element method. Analysis of this type of error is very useful in choosing an acurate and efficient integration method. Using the error approximation and an automatic step size control, the Modified Euler combine with Runge-Kutta 2nd order is the most acurate and efficient.